2018
DOI: 10.1016/j.ifset.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal and high-pressure treatments on the antirotaviral activity of human milk fractions

Abstract: Rotaviral gastroenteritis is associated with high rate of infant mortality and morbidity. Antirotaviral activity has been associated with some glycoproteins, such as immunoglobulins A (IgA), lactoferrin (LF), mucins and lactadherin of human milk. Although holder pasteurization (HoP, 63 ºC for 30 min) is the treatment currently applied to human milk, it might may lead to a decrease of its bioactive properties. The antirotaviral capacity of human milk appears showed to be mainly associated with the whey fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Moreover, recently obtained results suggest that anHPP treatment, at pressures below 600 MPa for 15 min, allows the antirotaviral activity to be retained (34).…”
Section: State Of the Art And Future Trendsmentioning
confidence: 99%
“…Moreover, recently obtained results suggest that anHPP treatment, at pressures below 600 MPa for 15 min, allows the antirotaviral activity to be retained (34).…”
Section: State Of the Art And Future Trendsmentioning
confidence: 99%
“…85 With regard to the effect of the tested treatments on the antirotaviral activity of the enriched dairy preparations, the results of this study showed that HHP conditions corresponding to those considered alternative to thermal pasteurization have not caused significant reduction in their RV neutralizing potential, in agreement with previous observations. 86 More specifically, we found that the neutralization values resulting after thermal pasteurization (75 °C for 20 s) and HHP treatment (500 MPa for 10 min or 600 MPa for 5 min) were above 90% except for WH + 0.5 IgG (82.8%). Therefore, HHP treatment could be considered safe with regard to the preservation of high antirotaviral activity.…”
Section: Discussionmentioning
confidence: 77%
“…Nebbia et al (2020) studied HTST (72 °C for 15 seconds) as an alternative to Holder pasteurization (62.5 °C for 30 minutes) to increase the preservation of bioactive compounds in human milk, noting that there was an increase in proteins on the surface of blood cells fat after pasteurization, to a lesser extent in HTST than in Holder pasteurization. Parrón et al (2018) evaluated in their study different pasteurization treatments, such as standard (62.5 C for 30 minutes), HTST (75 ° C for 20 seconds) and high pressure (600 MPa for 15 minutes) in human milk, on its components such as immunoglobulin A (IgA), lactoferrin, mucins and lactaderine. In conclusion, HTST and high pressure pasteurization treatments were less harmful to these components, that is, reducing smaller quantities, than standard pasteurization.…”
Section: High Temperature and Short Time (Htst)mentioning
confidence: 99%